Perancangan Sistem Otomatisasi Pengisian Air Galon Menggunakan Sensor Infrared Proximity - Gita Aubreza Safitri; Ana Nur Avivah; Enggar Bagus Pramudyanto; Rio Umair Andica; Eli Mas’idah (Journal of Engineering and Applied Technology, 2026)
The need for a practical, hygienic, and efficient drinking water dispensing system has driven the development of sensor-based automated devices to replace the manual mechanisms still widely used in conventional gallon pumps. This study aims to design and implement an automated water-filling system for water jugs using an infrared proximity sensor as an object detector and a relay module to control a DC water pump. The method employed is an empirical experiment involving the design, assembly, implementation, and testing of a prototype. The system is designed using direct control principles without a microcontroller, resulting in a simple, economical, and easily replicable architecture. Testing was conducted by simulating actual usage conditions to evaluate the sensor’s detection capability, relay response, pump stability, operational safety, energy efficiency, hygiene of use, and the economic aspects of the design. The results of the study show that the system is capable of consistently detecting the presence of a glass, automatically activating the pump when an object is detected, and stopping the water flow when the object is no longer within the sensor’s range. The system also demonstrates good reliability, low power consumption, and relatively affordable design costs. These findings indicate that the integration of infrared proximity sensors and relays can be an effective solution to support the automation of water jug filling in both household and public facility settings.